A Modified Implementation Mapping Methodology for Evaluating and Learning From Existing Implementation - Schultes, Marie-Therese; Albers, Bianca; Caci, Laura; Nyantakyi, Emanuela; Clack, Lauren (Frontiers in Public Health, 2022)
When empirically supported interventions are implemented in real-world practice settings, the process of how these interventions are implemented is highly relevant for their potential success. Implementation mapping is a method that provides step-by-step guidance for systematically designing implementation processes that fit the respective intervention and context. It includes needs assessments among relevant stakeholders, the identification of implementation outcomes and determinants, the selection and design of appropriate implementation strategies, the production of implementation protocols and an implementation outcome evaluation. Implementation mapping is generally conceptualized as a tool to prospectively guide implementation. However, many implementation efforts build on previous or ongoing implementation efforts, i.e., “existing implementation”. Learnings from existing implementation may offer insights critical to the success of further implementation activities. In this article, we present a modified implementation mapping methodology to be applied when evaluating existing implementation. We illustrate the methodology using the example of evaluating ongoing organized colorectal cancer screening programs in Switzerland. Through this example, we describe how we identify relevant stakeholders, implementation determinants and outcomes as well as currently employed implementation strategies. Moreover, we describe how we compare the types of strategies that are part of existing implementation efforts with those that implementation science would suggest as being suited to address identified implementation determinants. The results can be used for assessing the current state of implementation outcomes, refining ongoing implementation strategies, and informing future implementation efforts.